Cost analysis of treatment for periodontitis stages I–IV based on periodontal status and number of visits: a retrospective study at the Dental Teaching Hospital - B., Aysha Azzahra; Sulijaya, Benso; Soeroso, Yuniarti; Haerani, Natalina; Tadjoedin, Fatimah Maria; Rahardjo, Anton (Frontiers in Dental Medicine, 2025)
BackgroundPeriodontitis affects 20%–50% of the global population and 74.1% of the population in Indonesia, with 1.1 billion cases worldwide in 2019. Assessing treatment costs is essential to ensure affordability and optimize outcomes, particularly in developing countries.ObjectiveThis study aimed to estimate the treatment cost for stage I–IV periodontitis, evaluate changes in periodontal parameters [plaque index (PI), papillary bleeding index (PBI), and calculus index (CI)], and analyze both the relationship and differences between treatment cost, number of visits, and changes in periodontal status.Materials and methodsA retrospective observational study of 64 patient records (2020–2022) from the Periodontology Clinic, Universitas Indonesia Dental Hospital, was conducted. The medical records of single-visit patients or patients who lacked data on the periodontal variables in their medical records were excluded. Data included treatment costs (during the initial, surgical, and supportive phases), number of visits, and periodontal parameters (PI, PBI, and CI). A univariate analysis was performed to describe the distribution of the treatment cost, number of visits, and periodontal parameters. A bivariate analysis was conducted using Pearson’s correlation to examine the association between treatment cost, number of visits, and changes in periodontal parameters, while one-way ANOVA was used to assess differences in the mean periodontal changes among the groups with different treatment costs and number of visits, with a significance threshold of p < 0.05. The statistical analyses were performed using SPSS 26.0.ResultsThe univariate analysis showed that the highest mean cost was incurred by those with stage IV periodontitis (USD 50.45), while the lowest was incurred by those with stage III periodontitis (USD 18.96). Regarding the treatment phases, the surgical phase incurred the highest mean cost (USD 61.21), whereas the initial phase incurred the lowest (USD 20.08). The bivariate analysis using Pearson’s correlation indicated no significant associations between treatment cost or number of visits and changes in PI, PBI, or CI (p > 0.05). Similarly, the one-way ANOVA revealed no significant differences in mean changes in PI, PBI, and CI across the groups based on treatment cost and number of visits (p > 0.05).ConclusionTreatment cost and number of visits showed no significant association with periodontal status, suggesting that clinical outcomes are determined by treatment quality rather than expenditure or frequency of visits.